Baffle Diffraction in Interferometric Detectors of Gravitational Waves - Giuseppe Pelosi; Leonardo Possenti; Stefano Selleri; Innocenzo M. Pinto (Applied Computational Electromagnetics Society Journal (ACES), 2021)
This paper presents an efficient highfrequency analysis framework for studying diffraction occurring at irises, or baffles, in the arms of a Fabry- Perot optical interferometer, relevant to the design and operation of interferometric detectors of gravitational waves like LIGO and Virgo.